EXPLORING EFFECTIVE CLASSROOM MANAGEMENT STRATEGIES OF EFL TEACHERS IN JUNIOR HIGH SCHOOLS: CHALLENGES AND SOLUTIONS - Azzahra Siti Fatima; Hasriani G; Asriati Asriati (Universitas Negeri Makassar, 2026)
This study aims to explore the challenges faced by English teachers in improving learning effectiveness through classroom management in EFL classrooms at the junior high school level. The study focuses on (1) identifying the main challenges encountered by teachers in managing EFL classrooms and (2) examining the strategies implemented by teachers to overcome these challenges and improve learning effectiveness. This research employed a descriptive qualitative research design conducted at SMPN 18 Makassar. The participants of the study were two English teachers selected through purposive sampling. Data were collected through classroom observations and semi-structured interviews. The data were analyzed using the qualitative data analysis model proposed by Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings revealed that teachers faced several challenges, including students’ low basic English proficiency, lack of attention, discipline, and participation, differences in students’ characteristics and learning readiness, difficulties in using English as the medium of instruction, and school environmental factors. To address these challenges, teachers applied several strategies such as establishing classroom rules and agreements, using engaging activities, gradually using English during instruction, providing appreciation and motivation, and implementing group or pair work. These strategies helped create a more conducive classroom environment, maintain classroom control, and improve student engagement and learning effectiveness in EFL classrooms.